An Elective Course Exploring Occupational Justice Through Occupational Storytelling and Story Making - Julie Bednarski (Scholarworks @ WMU, 2016)
The purpose of this study was to examine whether second-year Master of Occupational Therapy (MOT) students who enroll in the elective course "Occupation in Long-Term Care (LTC)" would be able to apply concepts of occupational justice in the nursing home environment through engaging residents in occupational storytelling and story making in order to facilitate resident self-advocacy for participation in a valued occupation. The occupational therapy elective course was developed and implemented with students alternating between the classroom and the nursing home environments. Outcome evaluation measurements included analysis of student reflective journaling to obtain qualitative data. The researcher found that students are able to understand the concepts and issues of occupational justice in the nursing home population and apply knowledge to facilitate the resident's participation in meaningful occupations.